Manajemen Waktu Terhadap Kesiapan Asesmen Nasional - Fitriya, Madinatul; Mastur, Ali (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Time management is a student's effort to manage all activities carried out, but it cannot be said that they can control time if activities and work are often delayed. If a student implements time management well, there will be many positive impacts on all activities running on time and being completed on time. Therefore, this research aims to analyze the implementation of time management on the national assessment readiness of class XII MIPA students at SMA Wachid Hasyim 1 Surabaya. This research uses qualitative methods with results showing that implementing good time management by making educators and students more active and punctual in implementing learning activities will result in students being better prepared to face national assessments. SMA Wachid Hasyim 1 Surabaya class study time at school, there is an additional 2 hours of learning and there is an example of discipline from the teachers.